2017
DOI: 10.1177/0049475517691878
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis and thrombocytopenia: markers of dengue mortality

Abstract: Dengue fever is of great concern to public health in India as it contributes significantly to the burden of healthcare. The aim of our study was to measure mortality in dengue and its association with hepatitis and thrombocytopenia. Our study was performed in a tertiary care setting in the state of Kerala in southern India. Adult patients admitted in the year 2013 were included. Among 1308 confirmed dengue patients, the mortality rate was 1.76%. Hepatitis and thrombocytopenia were present in over 80% of all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
11
0
4
Order By: Relevance
“…5 A recent report from Kerala state of South India reported 1.76% mortality among 1308 cases of dengue. 10 From our review of literature, we have found that there are several predictors of mortality in patients with Dengue. We have excluded the common and non-specific manifestations like fever, headache, arthralgia, myalgia and abdominal pain from our analysis.…”
Section: -35mentioning
confidence: 98%
See 1 more Smart Citation
“…5 A recent report from Kerala state of South India reported 1.76% mortality among 1308 cases of dengue. 10 From our review of literature, we have found that there are several predictors of mortality in patients with Dengue. We have excluded the common and non-specific manifestations like fever, headache, arthralgia, myalgia and abdominal pain from our analysis.…”
Section: -35mentioning
confidence: 98%
“…This was similar to the results reported by Krishnamoorthy et al (p value = 0.015). 10 Thrombocytopenia is a marker of clinical severity as per WHO guidelines. 11,12 It was found that markedly elevated transaminases (>200U/L) showed a significant association with mortality.…”
Section: -35mentioning
confidence: 99%
“…No entanto, vale ressaltar que esse é um sinal clínico que aparece mais tardiamente sendo mais frequente em pacientes com dengue grave, demonstrando a ineficácia desse parâmetro para predizer evolução desfavorável. A baixa prevalência desse sinal no presente estudo justifica-se pelo fato de que a população avaliada foi de pacientes em potencial evolução para as formas graves da dengue (KRISHNAMOORTHY S, et al, 2017). Desde a década de 1970, a dengue era classificada em dengue indiferenciada, dengue clássica, febre hemorrágica da dengue (FHD) e síndrome do choque da dengue.…”
Section: Discussionunclassified
“…14 In another study done by Krishnamoorthy et al the case fatality ratio was 1.8%. 15 In WHO manual, it was highlighted that, if untreated the fatality was 30 to 40% in patients with DSS. 16 It is worthwhile to note that the survival of dengue infected children is directly related to early and intensive management.…”
Section: Discussionmentioning
confidence: 99%